Secondary battery and power consuming device including the same
Patent Information
- Application Number
- JP2022552957
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-12-27
- Publication Date
- 2025-03-06
- Estimated Expiration
- 2041-12-27
Smart Images

Figure 0007641293000003 
Figure 0007641293000004 
Figure 0007641293000005
Abstract
Description
[Technical field]
[0001] The present application relates to the technical field of batteries, and in particular to secondary batteries and power consuming devices including the same. [Background technology]
[0002] In recent years, secondary batteries have been widely used in energy storage power systems such as hydroelectric, thermal, wind and solar power stations, as well as in many fields such as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace, etc. As secondary batteries have been developed rapidly, the requirements for their energy density, electrochemical properties, etc. are also becoming higher.
[0003] Therefore, how to achieve both high energy density and good cycle characteristics in a battery is an issue that must be resolved as soon as possible in this field. Summary of the Invention
[0004] The present application has been made in view of the above-mentioned problems, and has an object to provide a secondary battery that achieves both high energy density and good cycle characteristics.
[0005] In order to achieve the above object, the present application provides a secondary battery and a power consuming device including the same.
[0006] The first aspect of the present application is A negative electrode plate, the negative electrode plate comprising: A negative electrode current collector; a first negative electrode film layer provided on at least one surface of the negative electrode current collector; a second negative electrode film layer provided on a surface of the first negative electrode film layer; the first negative electrode film layer includes a first negative electrode active material and a first conductive agent, the first negative electrode active material includes a silicon-based material; The secondary battery includes a silicon-based material having a mass ratio of 30% or more in the first negative electrode film layer, and a first conductive agent having a mass ratio of 25% or more in the first negative electrode film layer.
[0007] The secondary battery of the present invention can achieve both high energy density and good cycle characteristics.
[0008] In any embodiment, the mass ratio of the silicon-based material in the first negative electrode film layer may be 30% to 60%, preferably 40% to 50%. When the content of the silicon-based material is within the above range, the secondary battery using the negative electrode plate of the present application has a higher energy density.
[0009] In any embodiment, the mass ratio of the first conductive agent in the first negative electrode film layer may be 25% to 40%, preferably 28% to 35%. By using the first conductive agent in the above content range, the cycle characteristics of the battery can be further improved.
[0010] In any embodiment, the first conductive agent comprises one or more of superconducting carbon, acetylene black, ketjen black, conductive carbon black, graphene, carbon dots, carbon nanotubes, carbon nanofibers, and graphite, and preferably, the first conductive agent comprises one or more of conductive carbon black, graphite, and carbon nanotubes.
[0011] In an optional embodiment, the first conductive agent may include conductive carbon black, and the mass ratio of the first negative electrode film layer may be 20% or more, for example, 20% to 40%, or 23% to 35%.
[0012] In an optional embodiment, the first conductive agent may include carbon nanotubes, and the mass ratio of the first negative electrode film layer may be 0.4% or less, for example, 0.1% to 0.3%.
[0013] In an optional embodiment, the first conductive agent contains graphite, and the graphite has a volume average particle size Dv50 of 8 μm or less, preferably 2 μm to 5 μm. When the first conductive agent contains graphite with a particle size in a specific range, the cycle characteristics of the battery can be further improved.
[0014] In an optional embodiment, the first conductive agent contains graphite, and the mass ratio of the graphite in the first conductive agent is 10% or less, preferably 3% to 8%.
[0015] In any embodiment, the first negative electrode film layer may include a first binder, and a mass ratio of the first binder in the first negative electrode film layer may be 15% or more, preferably 18% to 25%.
[0016] In an optional embodiment, the ratio of the thickness of the first negative electrode film layer to the thickness of the second negative electrode film layer is 1:2 or less, preferably 1:12 to 1:3.
[0017] In an optional embodiment, the first negative electrode film layer has a thickness of 15 μm or less, preferably 5 μm to 13 μm.
[0018] In any embodiment, the ratio of the areal density of the first negative electrode film layer to the areal density of the second negative electrode film layer is 1:3 or less, preferably 1:9 to 1:3.
[0019] In an optional embodiment, the second negative electrode film layer comprises a second negative electrode active material, the second negative electrode active material comprises artificial graphite, and preferably, a mass ratio of the artificial graphite in the second negative electrode active material is 80% or more.
[0020] In an optional embodiment, the artificial graphite has a volume average particle size Dv50 of 10 μm to 20 μm, preferably 13 μm to 18 μm.
[0021] In any embodiment, the artificial graphite has a Dn10 of 1 μm to 5 μm, preferably 2 μm to 3 μm.
[0022] In any embodiment, the specific surface area BET of the artificial graphite is 0.5 m 2 / g~1.5m 2 / g, preferably 0.6m 2 / g~1.0m 2 / g.
[0023] In any embodiment, the initial coulombic efficiency of the artificial graphite is between 94.5% and 96.5%, preferably between 95.0% and 96.0%.
[0024] In any embodiment, the second negative electrode active material further comprises a silicon-based material, and preferably, the mass ratio of the silicon-based material in the second negative electrode film layer is 8% or less. The silicon-based material is used in a specific content in the second negative electrode active material, which can further improve the cycle characteristics of the battery.
[0025] A second aspect of the present application further provides a power consuming device including the secondary battery of the first aspect of the present application. [Brief description of the drawings]
[0026] [Figure 1] FIG. 2 is a schematic diagram of a cross section of a negative electrode plate according to one embodiment of the present application. [Diagram 2] 1 is a scanning electron microscope photograph of a cross section of a negative plate of one embodiment of the present application, where the bright areas in the figure are silicon-based materials. [Diagram 3] FIG. 3 is a partially enlarged view of FIG. 2 taken by a scanning electron microscope. [Figure 4] FIG. 1 is a schematic diagram of a secondary battery according to an embodiment of the present application. [Diagram 5] 5 is an exploded view of the secondary battery according to the embodiment of the present application shown in FIG. 4. [Figure 6] FIG. 1 is a schematic diagram of a battery module according to an embodiment of the present application. [Figure 7] FIG. 1 is a schematic diagram of a battery pack according to an embodiment of the present application. [Figure 8] FIG. 8 is an exploded view of the battery pack shown in FIG. 7 according to the embodiment of the present application. [Figure 9] 1 is a schematic diagram of a power consumption device powered by a secondary battery according to an embodiment of the present application; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] Hereinafter, with reference to the drawings as appropriate, embodiments specifically disclosing the negative electrode plate, its manufacturing method, secondary battery, and power consumption device of the present application will be described in detail. However, unnecessary detailed description may be omitted. For example, detailed description of known matters and repeated description of substantially the same structure may be omitted. This is to avoid the following description becoming unnecessarily long and to make it easy for those skilled in the art to understand. In addition, the drawings and the following description are provided to enable those skilled in the art to fully understand the present application, and are not intended to limit the subject matter described in the claims.
[0028] The "ranges" disclosed herein are defined in the form of lower and upper limits, and a given range is defined by selecting one lower limit and one upper limit, with the selected lower and upper limits defining the boundaries of the particular range. The ranges thus defined may or may not include the endpoint values and may be arbitrarily combined, i.e., any lower limit and any upper limit may be combined to form a range. For example, if ranges of 60-120 and 80-110 are listed for a particular parameter, it is understood that the ranges of 60-110 and 80-120 are also contemplated. Also, if 1 and 2 are listed as the minimum range values and 3, 4, and 5 are listed as the maximum range values, all of the ranges of 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5 are contemplated. In this application, unless otherwise specified, the numerical range "a-b" represents a shorthand notation for any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers contained within "0-5" are listed herein, with "0-5" being merely shorthand for combinations of these numerical values. Also, when a parameter is described as an integer ≧2, this is equivalent to disclosing that the parameter is, for example, the integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0029] Unless otherwise specified, all the embodiments and preferred embodiments in the present application can be combined with each other to form a new technical solution.
[0030] Unless otherwise specified, all technical features and preferred technical features of the present application can be combined with each other to form a new technical solution.
[0031] Unless otherwise specified, all steps in the present application may be performed in sequence or randomly, but are preferably performed in sequence. For example, the method includes steps (a) and (b) indicating that the method may include steps (a) and (b) performed in sequence, or may include steps (b) and (a) performed in sequence. For example, the method may further include step (c) indicating that step (c) can be added to the method in any order, for example, the method may include steps (a), (b) and (c), may include steps (a), (c) and (b), may include steps (c), (a) and (b), etc.
[0032] Unless otherwise specified, the terms "comprise" and "inclusion" in this application may be open or closed. For example, the terms "comprise" and "inclusion" may indicate that the term may further include or include other components not listed, or that the term may include or include only the components listed.
[0033] In this application, unless otherwise specified, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition A is true (or exists) and B is false (or does not exist), the condition A is false (or does not exist) and B is true (or exists), or the condition A and B are both true (or exist) all satisfy the condition "A or B."
[0034] [Secondary battery] A first aspect of the present application provides a secondary battery including the following negative electrode plate:
[0035] A secondary battery is also called a rechargeable battery or a storage battery, and refers to a battery that can continue to be used after being discharged by activating the active material through charging.
[0036] Typically, a secondary battery pack includes positive and negative plates, a separator, and an electrolyte. During the charge and discharge process of the battery, active ions (e.g., lithium ions) shuttle between the positive and negative plates to insert and remove themselves. The separator is placed between the positive and negative plates and mainly serves to prevent short circuits between the positive and negative plates, and also allows the active ions to pass through. The electrolyte is placed between the positive and negative plates and mainly serves to transport the active ions.
[0037] [Negative plate] One embodiment of the present application is A negative electrode current collector; a first negative electrode film layer provided on at least one surface of the negative electrode current collector; A second negative electrode film layer provided on a surface of the first negative electrode film layer; the first negative electrode film layer includes a first negative electrode active material and a first conductive agent, the first negative electrode active material includes a silicon-based material; The present invention provides a negative electrode plate, in which the mass ratio of the silicon-based material in the first negative electrode film layer is 30% or more, and the mass ratio of the first conductive agent in the first negative electrode film layer is 25% or more.
[0038] Although the mechanism is still unclear, the applicant unexpectedly found that when the silicon content in the first negative electrode film layer is high, the energy density and cycle characteristics of the produced battery can be improved by using a high content of conductive agent.
[0039] By setting the mass ratio of the first conductive agent in the first negative electrode film layer within the range of the present application, the capacity of the silicon-based material in the first negative electrode film layer can be effectively ensured, and this is also advantageous for improving the cycle characteristics of the battery.
[0040] In some embodiments, the negative electrode current collector may include a metal foil or a composite current collector. For example, a copper foil may be used as the metal foil. The composite current collector may include a polymeric substrate and a metal layer formed on at least one surface of the polymeric substrate. The composite current collector may be formed by forming a metal material (such as copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys) on a polymeric substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0041] In some embodiments, the first negative electrode active material comprises a silicon-based material, which may be one or more selected from elemental silicon, silicon oxide (e.g., silicon monoxide), silicon carbon composite, silicon nitrogen composite, silicon alloy, and prelithiated silicon oxide, preferably one or more of elemental silicon, silicon carbon composite, silicon oxide, and prelithiated silicon oxide, more preferably one or more of prelithiated silicon oxide, silicon oxide, and silicon carbon composite.
[0042] In some embodiments, the mass ratio of the silicon-based material in the first negative electrode film layer may be 30% or more, preferably 30% to 60%, more preferably 40% to 50%. By ensuring that the content of the silicon-based material is within a predetermined range, the probability of wrinkles on the electrode plate can be effectively reduced while ensuring that the battery has a high energy density, and the separation of the first negative electrode film layer from the current collector and the second negative electrode film layer can also be reduced, thereby further improving the cycle characteristics of the battery.
[0043] In some embodiments, the first conductive agent comprises one or more of superconducting carbon, acetylene black, ketjen black, conductive carbon black, graphene, carbon dots, carbon nanotubes, carbon nanofibers, and graphite, preferably, the first conductive agent comprises one or more of conductive carbon black, graphite, and carbon nanotubes.
[0044] In some embodiments, the mass ratio of the first conductive agent in the first negative electrode film layer may be 25% or more, for example, 26-40%, 28-35%. Through research, the inventors unexpectedly found that when the content of the first conductive agent in the first negative electrode film layer exceeds a certain content, a porous buffer structure with high conductivity and high elasticity is formed in the first negative electrode film layer, which can effectively buffer the expansion of silicon-based materials and further improve the cycle characteristics of the battery.
[0045] In the present application, the scanning electron microscope test on the negative plate may be performed by any method commonly used in the art, for example, using a ZEISS sigma 300 scanning electron microscope and then testing according to standard JY / T010-1996.
[0046] In some embodiments, the first conductive agent may include conductive carbon black, and the mass ratio of the first negative electrode film layer may be 20% or more, for example, 20% to 40%, or 23% to 35%.
[0047] In some embodiments, the first conductive agent may include carbon nanotubes, and the mass ratio of the first negative electrode film layer may be 0.4% or less, for example, 0.1% to 0.3%.
[0048] In some embodiments, the silicon-based material has a volume average particle size Dv50 of 3 μm to 10 μm, preferably 4 μm to 8 μm.
[0049] In some embodiments, the first conductive agent comprises graphite, which may be artificial graphite and / or natural graphite.
[0050] In some embodiments, the graphite has a volume average particle size Dv50 of 8 μm or less, preferably 2 μm to 5 μm.
[0051] In some embodiments, the first conductive agent comprises artificial graphite.
[0052] In some embodiments, the mass ratio of the graphite in the first conductive agent is 10% or less, preferably 3% to 8%.
[0053] In some embodiments, the first negative electrode film layer includes a first binder, and the mass ratio of the first binder in the first negative electrode film layer is 15% or more, preferably 18% to 25%.
[0054] In some embodiments, the first binder may be at least one selected from styrene butadiene rubber (SBR), polyacrylic acid (PAA), polyacrylonitrile (PAN), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS), such as at least one selected from styrene butadiene rubber (SBR) and polyacrylic acid (PAA).
[0055] In some embodiments, the first negative electrode membrane layer may preferably include other auxiliary agents, such as a dispersing agent (eg, carboxymethylcellulose or its sodium salt (CMC-Na)).
[0056] In the present application, as will be understood, the total of each component in the first negative electrode membrane layer (eg, the first negative electrode active material, the first conductive agent, the first binder, and any other auxiliary agents) is 100% by mass.
[0057] In some embodiments, the thickness of the first negative electrode film layer is 15 μm or less, preferably 5 μm to 13 μm. Since the silicon content in the first negative electrode film layer is high, the thickness of the first negative electrode film layer is in a predetermined range, which reduces the expansion of the first negative electrode film layer and reduces the risk of separation from the current collector and the second negative electrode film layer, and further improves the cycle characteristics of the battery.
[0058] In some embodiments, the ratio of the thickness of the first negative electrode film layer to the thickness of the second negative electrode film layer may be 1:2 or less, for example, 1:12 to 1:3, or 1:10 to 1:4. By setting the thicknesses as described above, the capacity of the first negative electrode film layer is ensured while reducing side reactions between the first negative electrode film layer and the electrolyte.
[0059] In some embodiments, the ratio of the surface density of the first negative electrode film layer to the surface density of the second negative electrode film layer is 1:3 or less, preferably 1:9 to 1:3.
[0060] In some embodiments, the areal density of the first negative electrode film layer is 0.649 to 2.922 mg / cm 2 , preferably 0.974 to 2.597 mg / cm 2 It is.
[0061] In the present application, the areal density of the negative electrode film layer has a definition known in the art and may be tested by a method known in the art. For example, a negative electrode plate coated on one side and cold pressed (in the case of a negative electrode plate coated on both sides, the negative electrode active material layer on one side may be wiped off) is punched out into a small disk with an area of S1, and its weight is weighed and recorded as M1. Next, the negative electrode active material layer of the weighed negative electrode plate is wiped off, and the weight of the negative electrode current collector is weighed and recorded as M0, and the areal density of the negative electrode active material layer = (weight of negative electrode plate M1 - weight of negative electrode current collector M0) / S1. In order to ensure the accuracy of the test results, multiple sets (for example, 10 sets) of test samples may be tested and the average value may be calculated as the test result.
[0062] In some embodiments, the second anode membrane layer comprises a second anode active material, and the second anode active material comprises artificial graphite.
[0063] In some embodiments, the mass ratio of the artificial graphite in the second negative electrode film layer may be 80% or more, for example, 80% to 100%, or 90% to 95%.
[0064] In some embodiments, the artificial graphite has a volume average particle size Dv50 of 10 μm to 20 μm, preferably 13 μm to 18 μm.
[0065] In some embodiments, the artificial graphite has a Dn10 of 1 μm to 5 μm, preferably 2 μm to 3 μm. If Dn10 is too small, the electrolyte diffusion channels are clogged, and the capacity of the first negative electrode film layer is affected. If Dn10 is too large, the tap density of the second negative electrode film layer is too low, the electrolyte diffusion channels are too large, and the second negative electrode film layer loses its protective effect on the first negative electrode film layer.
[0066] The Dn10 and Dv50 of the negative active material may be measured using a laser particle size analyzer (e.g., Malvern Master Size 3000) in accordance with standard GB / T 19077.1-2016. The physical definitions of Dn10 and Dv50 are as follows:
[0067] Dn10 is the particle size when the cumulative particle number distribution rate of the negative electrode active material reaches 10%, Dv50 is the particle size when the cumulative volume distribution rate of the negative electrode active material reaches 50%.
[0068] In some embodiments, the specific surface area of the artificial graphite is 0.5 to 1.5 m 2 / g, preferably 0.6 to 1.0 m 2 The specific surface area of the artificial graphite in the second negative electrode film layer being within the predetermined range is advantageous for further improving the initial efficiency and cycle characteristics of the battery.
[0069] In the present application, the specific surface area of a material has a definition known in the art and may be measured by instruments and methods known in the art, for example, in accordance with GB / T 19587-2017 Standard for Measuring the Specific Surface Area of Solid Materials by Gas Adsorption BET Method, a test is performed according to a nitrogen adsorption specific surface area analysis test method, and calculation is performed according to the BET (Brunauer Emmett Teller) method, and the nitrogen adsorption specific surface area analysis test may be performed by a Tri StarII 3020 specific surface and porosity analyzer manufactured by Micromeritics, Inc., USA.
[0070] In some embodiments, the initial coulombic efficiency of the artificial graphite is between 94.5% and 96.5%, preferably between 95.0% and 96.0%.
[0071] The initial coulombic efficiency of artificial graphite has a definition known in the art and may be measured by methods known to those skilled in the art. For example, artificial graphite, conductive agent Super P, binder SBR, and dispersant CMC are dispersed in deionized water in a weight ratio of 94.5:1.5:2.5:1.5, thoroughly stirred and mixed to form a uniform slurry, and the slurry is applied onto a collector copper foil, dried and cold pressed, and then punched into a disk with a diameter of 14 mm for use. A 14 mm lithium sheet is used as the counter electrode. EC, DEC, and DMC are uniformly mixed in equal volumes, and then 1 mol / L LiPF6 is uniformly dissolved in the organic solvent to form an electrolyte. The artificial graphite disk, separator, and lithium sheet are stacked in this order to produce an electrode group, and the electrolyte is injected into the electrode group to complete the manufacture of a button battery. The above operations are performed in a glove box.
[0072] A button battery is placed in a constant temperature environment of 25°C and discharged at a constant current of 0.1C to a voltage of 0.005V, then discharged at a constant voltage of 0.005V until the current falls to 0.01mA or less, and then left to stand for 5 minutes. The discharge capacity at this point is designated as d0, and the battery is then charged at a constant current of 0.1C to a voltage of 2.0V. The charge capacity at this point, which is the initial specific capacity, is designated as c0, and the initial coulombic efficiency ice0 = c0 / d0 × 100%.
[0073] In some embodiments, the second negative electrode active material may further include a silicon-based material, which may be one or more selected from elemental silicon, silicon oxide (e.g., silicon monoxide), silicon carbon composite, silicon nitrogen composite, silicon alloy, and prelithiated silicon oxide, preferably one or more of elemental silicon, silicon carbon composite, silicon oxide, and prelithiated silicon oxide, more preferably one or more of prelithiated silicon oxide, silicon oxide, and silicon carbon composite.
[0074] In some embodiments, when the second negative electrode active material includes a silicon-based material, the mass ratio of the silicon-based material in the second negative electrode film layer may be 8% or less, for example, 1% to 7%, 2% to 6%. By adding a certain amount of silicon-based material to the second negative electrode active material, the silicon content of the entire electrode plate is improved, while ensuring synchronization of the expansion / contraction of the first negative electrode film layer and the second negative electrode film layer, reducing the interaction force between the film layers, improving the problem of delamination between the first negative electrode film layer and the second negative electrode film layer, and further improving the cycle characteristics of the battery.
[0075] In some embodiments, when the second negative electrode active material includes a silicon-based material, the weight ratio of the silicon-based material in the first negative electrode film layer and the second negative electrode film layer is 1:1 to 5:1, preferably 1:1 to 3:1. By setting it as above, the synchronization of the contraction or expansion of the two layers is further ensured, the separation of the two film layers is effectively reduced, and the cycle characteristics of the battery are further improved.
[0076] In some embodiments, the second negative electrode film layer includes a second conductive agent, the second conductive agent includes one or more of superconducting carbon, acetylene black, ketjen black, conductive carbon black, graphene, carbon dots, carbon nanotubes, carbon nanofibers, and graphite, preferably one or more of acetylene black, ketjen black, and conductive carbon black, more preferably one or more of acetylene black and conductive carbon black. Preferably, the mass ratio of the second conductive agent in the second negative electrode film layer may be 0.5% to 10%, for example, 0.6% to 5%, or 0.8% to 2.5%.
[0077] In some embodiments, the second negative electrode membrane layer further includes a second binder, which may be at least one selected from styrene butadiene rubber (SBR), polyacrylic acid (PAA), polyacrylonitrile (PAN), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS), and is preferably styrene butadiene rubber (SBR) and polyacrylic acid (PAA). Preferably, the mass ratio of the second binder in the second negative electrode membrane layer is 0.1% to 6%, for example, 0.5% to 4%, 1% to 3%.
[0078] In some embodiments, the second negative electrode membrane layer preferably includes other additives, such as a dispersant (e.g., carboxymethylcellulose or its sodium salt (CMC-Na)). Preferably, the mass ratio of the other additives in the second negative electrode membrane layer may be 6% or less, for example, 0.1% to 5%, or 0.2% to 4%.
[0079] As will be understood in this application, the total of each component in the second negative electrode film layer is 100% by mass.
[0080] In some embodiments, the second negative electrode film layer has a thickness of 25 μm to 60 μm, preferably 30 μm to 50 μm. If the thickness of the second negative electrode film layer is within the above range, the first negative electrode film layer can be protected, but if the thickness is too thick, the capacity of the first negative electrode film layer is easily affected.
[0081] In some embodiments, the total thickness of one side of the negative plate is 28 μm to 90 μm, preferably 30 μm to 75 μm, where, as will be understood by those skilled in the art, the expression "total thickness of one side" does not include the thickness of the current collector, but refers to the total thickness of the first and second negative electrode film layers on one side of the current collector.
[0082] The above-mentioned parameters may be tested by sampling during the battery manufacturing process, or by sampling from a manufactured secondary battery.
[0083] When the test sample is sampled from a manufactured secondary battery, for example, the test sample may be sampled through the following steps.
[0084] (1) The secondary battery is discharged (for safety reasons, the battery is generally fully discharged), the battery is disassembled, the negative plate is removed, and the negative plate is immersed in dimethyl carbonate (DMC) for a predetermined time (e.g., 2 to 10 hours), and then the negative plate is removed and dried at a predetermined temperature and time (e.g., 40°C to 70°C, 2 hours to 5 hours), and then the negative plate is removed. At this time, the dried negative plate may be sampled to test each parameter related to the above-mentioned negative active material layer of the present application (e.g., areal density, tap density, thickness, etc. of the negative active material layer).
[0085] (2) The negative electrode plate dried in step (1) is baked at a predetermined temperature and time (e.g., 200-500°C, 1h-3h), and an arbitrary region is selected in the baked negative electrode plate, and the second negative electrode active material is sampled first (the powder may be scraped off with a blade for sampling), where the depth of the powder scraped off does not exceed the boundary region between the first negative electrode film layer and the second negative electrode film layer, and then the first negative electrode active material is sampled in the same manner. During the manufacturing process of the negative electrode active material layer, there may be a fusion layer (i.e., the first negative electrode active material and the second negative electrode active material are simultaneously present in the fusion layer) in the boundary region between the first negative electrode film layer and the second negative electrode film layer, and in consideration of the accuracy of the test, when sampling the first negative electrode active material, the fusion layer is first removed, and then the powder of the first negative electrode active material is scraped off for sampling.
[0086] (3) The first negative electrode active material and the second negative electrode active material collected in step (2) are respectively sieved (e.g., sieved through a 100-300 mesh screen), and finally, a first negative electrode active material sample and a second negative electrode active material sample are obtained, which can be used to test the parameters of each of the above materials of the present application (e.g., material morphology, particle size, specific surface area, etc.).
[0087] During the sampling process, an optical microscope or a scanning electron microscope may be used to assist in determining the location of the boundary region between the first and second negative electrode film layers.
[0088] In the present application, the mass ratio of silicon-based material in the negative electrode film layer may be measured using instruments and methods known in the art. For example, when the test sample is sampled from a manufactured secondary battery, the silicon-based material is obtained by the above steps, and the silicon-based material is decomposed according to EPA-3052-1996 "Microwave Acid Decomposition Method for Silicate", and then the silicon element content is measured using an ICAP-7000 type inductively coupled plasma optical emission spectrometer (ICP-OES) manufactured by Thermo Fisher Scientific, USA, according to EPA 6010D-2014 "Inductively Coupled Plasma Atomic Emission Spectroscopy". The specific test method is as follows: 0.5 g of a silicon-based material sample is decomposed in microwaves using 10 mL of 65% by mass nitric acid and 10 mL of 40% by mass hydrofluoric acid, then added to a 50 mL measuring flask to a constant volume, and the silicon element content is then measured using an ICAP-7000 ICP-OES, and the mass ratio of the silicon-based material is calculated from the silicon element content.
[0089] In the present application, the mass ratio of the binder and the dispersant in the negative electrode film layer may be measured simultaneously by instruments and methods known in the art. For example, when a test sample is sampled from a manufactured secondary battery, a powder material may be obtained by the above steps, and the mass ratio of the binder and the dispersant may be tested by thermogravimetric analysis (a thermogravimetric analyzer may be used as the test instrument).
[0090] In the present application, the mass ratio of the conductive agent in the negative electrode film layer may be measured by the equipment and method known in the art. For example, when the test sample is sampled from the manufactured secondary battery, the powder material is obtained by the above steps, and the mass ratio of the silicon-based material, the binder and the dispersant is tested by the above method, in which the mass ratio of the conductive agent=the mass ratio of the first negative electrode film layer-the mass ratio of the silicon-based material-the mass ratio of the binder-the mass ratio of the dispersant.
[0091] In addition, the parameters of the first and second negative electrode film layers described in this application, such as the thickness of the first negative electrode film layer, the thickness of the second negative electrode film layer or its surface density, tap density, etc., are all within the parameter range of the film layer on one side of the negative electrode plate. When the first and second negative electrode film layers are provided on both sides of the negative electrode current collector, if the parameters of the first or second negative electrode film layer on either one side satisfy the present application, it is deemed to be within the patent scope of this application. In addition, the ranges of the thickness, surface density, etc. of the negative electrode active material layer in this application are all parameters of the film layer that is tapped by cold pressing and used for assembling the battery.
[0092] In some embodiments, for example, the negative electrode plate may be manufactured as follows: first, each component in the first negative electrode film layer is dispersed in a solvent (e.g., deionized water) to form a negative electrode slurry 1, each component in the second negative electrode film layer is dispersed in a solvent (e.g., deionized water) to form a negative electrode slurry 2, and the negative electrode slurry 1 and the negative electrode slurry 2 are simultaneously extruded by a double cavity coating device, the negative electrode slurry 1 is applied onto a current collector to form a first negative electrode film layer, the negative electrode slurry 2 is applied onto the first negative electrode film layer to form a second negative electrode film layer, and finally, the negative electrode plate is obtained through processes such as baking and cold pressing.
[0093] [Positive plate] The positive electrode plate usually includes a positive electrode current collector and a positive electrode film layer provided on at least one surface of the positive electrode current collector, and the positive electrode film layer includes a positive electrode active material.
[0094] As an example, the positive electrode current collector has two surfaces opposing each other in the thickness direction, and the positive electrode film layer is provided on either one or both of the two opposing surfaces of the positive electrode current collector.
[0095] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, an aluminum foil may be used as the metal foil. The composite current collector may include a polymeric substrate and a metal layer formed on at least one surface of the polymeric substrate. The composite current collector may be formed by forming a metal material (such as aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy) on a polymeric substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE)).
[0096] In some embodiments, the positive electrode active material may be a positive electrode active material for batteries known in the art. As an example, the positive electrode active material may include at least one of a lithium-containing phosphate having an olivine structure, a lithium transition metal oxide, and a modified compound of each. However, the present application is not limited to these materials, and other conventional materials that can be used as a positive electrode active material for batteries can also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides include lithium cobalt oxide (e.g., LiCoO2), lithium nickel oxide (e.g., LiNiO2), lithium manganese oxide (e.g., LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (e.g., LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (simply NCM 333 (may also be referred to as LiNi 0.5 Co 0.2 Mn 0.3 O2 (simply NCM 523 (may also be referred to as LiNi 0.5 Co 0.25 Mn 0.25 O2 (simply NCM 211 (may also be referred to as LiNi 0.6 Co 0.2 Mn 0.2 O2 (simply NCM 622(may also be referred to as LiNi 0.8 Co 0.1 Mn 0.1 O2 (simply NCM 811 Lithium nickel cobalt aluminum oxide (e.g., LiNi 0.85 Co 0.15 Al 0.05 O2) and modified compounds thereof, but are not limited thereto. Examples of the lithium-containing phosphate having an olivine structure include, but are not limited to, at least one of lithium iron phosphate (e.g., LiFePO4 (which may be simply referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (e.g., LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, and a composite material of lithium manganese iron phosphate and carbon.
[0097] In some embodiments, the positive electrode membrane layer more preferably includes a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0098] In some embodiments, the positive electrode membrane layer more preferably includes a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0099] In some embodiments, the positive electrode plate may be manufactured as follows: The components for manufacturing the positive electrode plate, such as the positive electrode active material, conductive agent, binder, and other optional components, are dispersed in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry, and the positive electrode slurry is applied onto a positive electrode current collector, followed by processes such as baking and cold pressing to obtain a positive electrode plate.
[0100] [Electrolyte] The electrolyte serves to transport ions between the positive and negative electrodes. In the present application, the type of electrolyte is not particularly limited and may be selected as necessary. For example, the electrolyte may be liquid, gel, or completely solid.
[0101] In some embodiments, the electrolyte is in liquid form and includes an electrolyte salt and a solvent.
[0102] In some embodiments, the electrolyte salt may be at least one selected from lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bisfluorosulfonimide, lithium bistrifluoromethanesulfonate, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluoro(oxalato)borate, lithium bis(oxalato)borate, lithium difluorobis(oxalato)phosphate, and lithium tetrafluoro(oxalato)phosphate.
[0103] In some embodiments, the solvent may be at least one selected from ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.
[0104] In some embodiments, the electrolyte more preferably contains an additive. For example, the additive may include a negative electrode film-forming additive, a positive electrode film-forming additive, or an additive that can improve some characteristics of the battery, such as an additive that improves the overcharge characteristics of the battery, or an additive that improves the high-temperature or low-temperature characteristics of the battery.
[0105] [Separator] In some embodiments, the secondary battery further includes a separator. In the present application, the type of the separator is not particularly limited, and any known separator with a porous structure having good chemical stability and mechanical stability may be used.
[0106] In some embodiments, the separator may be made of at least one material selected from glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a single-layer thin film or a multi-layer composite thin film, and is not particularly limited. When the separator is a multi-layer composite thin film, the materials of the layers may be the same or different, and is not particularly limited.
[0107] In some embodiments, the positive plate, the negative plate, and the separator may be formed into an electrode assembly by a winding or lamination process.
[0108] In some embodiments, the secondary battery may include an exterior body that can be used to package the electrode assembly and the electrolyte.
[0109] In some embodiments, the exterior of the secondary battery may be a hard case, such as a hard plastic case, an aluminum case, a steel case, etc. The exterior of the secondary battery may be a soft pack, such as a bag soft pack, etc. The material of the soft pack may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0110] A second aspect of the present application further relates to a power consuming device including the secondary battery according to the first aspect of the present application.
[0111] In the present application, the shape of the secondary battery is not particularly limited, and may be cylindrical, rectangular, or any other shape. For example, FIG. 4 shows a secondary battery 5 having a rectangular structure according to an example.
[0112] In some embodiments, as shown in FIG. 5, the exterior body may include a case 51 and a cover plate 53. The case 51 may include a bottom plate and a side plate connected to the bottom plate, and a chamber is defined by the bottom plate and the side plate. The case 51 has an opening communicating with the chamber, and the cover plate 53 may cover the opening to seal the chamber. The positive electrode plate, the negative electrode plate and the separator may be formed into an electrode assembly 52 by a winding process or a stacking process. The electrode assembly 52 is packaged in the chamber. The electrolyte is impregnated into the electrode assembly 52. The number of electrode assemblies 52 included in the secondary battery 5 may be one or more, and may be selected by those skilled in the art according to specific practical needs.
[0113] In some embodiments, the secondary batteries may be assembled into a battery module, and the number of secondary batteries included in the battery module may be one or more, and the specific number may be determined by one skilled in the art depending on the application and capacity of the battery module.
[0114] Fig. 6 shows an example of a battery module 4. As shown in Fig. 6, in the battery module 4, a plurality of secondary batteries 5 may be arranged sequentially in the longitudinal direction of the battery module 4. Of course, the batteries may be arranged in any other manner. Furthermore, the plurality of secondary batteries 5 may be fixed together with a fastener.
[0115] Preferably, the battery module 4 may further include a housing having an accommodating space, and the multiple secondary batteries 5 may be accommodated in the accommodating space.
[0116] In some embodiments, the battery modules may also be assembled into a battery pack, and the number of battery modules included in the battery pack may be one or more, and the specific number may be determined by one skilled in the art according to the application and capacity of the battery pack.
[0117] 7 and 8 show a battery pack 1 according to an example. As shown in Fig. 7 and 8, the battery pack 1 may include a battery housing and a plurality of battery modules 4 provided in the battery housing. The battery housing may include an upper housing 2 and a lower housing 3, and the upper housing 2 may be covered by the lower housing 3 to form an enclosed space that houses the battery modules 4. The plurality of battery modules 4 may be arranged in the battery housing in any configuration.
[0118] The present application further provides a power consuming device including at least one of the secondary battery, battery module, or battery pack according to the present application. The secondary battery, battery module, or battery pack can be used as a power source for the power consuming device or as an energy storage unit for the power consuming device. The power consuming device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid vehicles, plug-in hybrid vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), trains, ships, satellites, energy storage systems, etc.
[0119] The power consumption device may be a secondary battery, a battery module or a battery pack according to the needs of the use.
[0120] 9 is an example of a power consuming device, such as a pure electric vehicle, a hybrid vehicle, or a plug-in hybrid vehicle, etc. A battery pack or a battery module may be used to meet the high power and high energy density needs of the secondary battery of the power consuming device.
[0121] [Example] The following examples of the present application are described. The examples described below are illustrative and are used only to interpret the present application, and should not be understood to limit the present application. In the examples, unless specific techniques or conditions are specified, the techniques, conditions or product instructions described in the literature in this field are followed. Unless the manufacturer is specified, the reagents or equipment used are all ordinary products available commercially.
[0122] [Secondary battery manufacturing] Example 1 1. Manufacturing of positive electrode plate: LiNi, the positive electrode active material 0.8 Co 0.1 Mn 0.1 O2(NCM 811 ), polyvinylidene fluoride (PVDF) as a binder, and acetylene black as a conductive agent were dissolved in N-methylpyrrolidone (NMP) as a solvent in a mass ratio of 97%:1.5%:1.5%, and the mixture was thoroughly stirred and mixed uniformly to produce a positive electrode slurry. The positive electrode slurry was then uniformly applied onto aluminum foil as a positive electrode current collector, and then baked, cold pressed, and cut to obtain a positive electrode plate.
[0123] 2. Manufacturing of negative electrodes Preparation of negative electrode slurry 1: Silicon monoxide, styrene butadiene rubber (SBR) as a binder, polyacrylic acid (PAA) as a binder, dispersant (CMC-Na), conductive carbon black (Super-P, SP), and carbon nanotubes (CNT) were mixed in a weight ratio of 40%:10%:8%:17%:24.7%:0.3% with sufficient stirring in an appropriate amount of deionized water to prepare negative electrode slurry 1. The volume average particle diameter Dv50 of silicon monoxide was 6.8 μm.
[0124] Preparation of negative electrode slurry 2: Artificial graphite, silicon monoxide, styrene butadiene rubber as a binder, polyacrylic acid, dispersant (CMC-Na), and conductive carbon black (Super-P) were mixed in a weight ratio of 90%:6%:1%:1.5%:0.5%:1% with an appropriate amount of deionized water and thoroughly stirred to prepare negative electrode slurry 2. The volume average particle diameter Dv50 of the artificial graphite was 14.7 μm and the specific surface area BET was 0.69 m.2 / g, Dn10 was 2.8 μm, the 0.1 C discharge capacity at 0.05 to 2.0 V was 357.8 mAh / g, and the initial coulombic efficiency was 95.9%.
[0125] Manufacture of negative electrode plate: Negative electrode slurry 1 and negative electrode slurry 2 were extruded simultaneously by a double cavity coating device. Negative electrode slurry 1 was coated on a negative electrode current collector to form a first negative electrode film layer, and negative electrode slurry 2 was coated on the first negative electrode film layer to form a second negative electrode film layer. Finally, the negative electrode plate was obtained after baking, cold pressing and cutting. The thickness of the first negative electrode film layer was 12.5 μm, and the surface density of the first negative electrode film layer was 1.95 mg / cm. 2 The thickness of the second negative electrode film layer is 48.5 μm, and the surface density of the second negative electrode film layer is 6.49 mg / cm 2 It was.
[0126] 3. Separator: Polypropylene film was used.
[0127] 4. Preparation of electrolyte: Ethylene carbonate (EC), methyl ethyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:1, and then LiPF6 was uniformly dissolved in the above solution to obtain an electrolyte, in which the concentration of LiPF6 was 1 mol / L.
[0128] 5. Manufacturing of secondary battery: The positive electrode plate, separator, and negative electrode plate are stacked in this order and wound to obtain an electrode assembly. The electrode assembly is placed in an outer casing, the electrolyte solution prepared above is injected, and the secondary battery is obtained through processes such as packaging, standing, chemical formation, and aging.
[0129] Comparative Example 1 For both negative electrode slurry 1 and negative electrode slurry 2, artificial graphite, silicon monoxide, styrene butadiene rubber as a binder, polyacrylic acid, thickener (CMC-Na), and conductive carbon black (Super-P) were mixed in a weight ratio of 80%:16%:1%:1.5%:0.5%:1% with an appropriate amount of deionized water and thoroughly stirred to produce a negative electrode slurry (the silicon content in the entire negative electrode film layer produced is the same as in Example 8). For the artificial graphite, the volume average particle diameter Dv50 was 14.7 μm and the specific surface area BET was 0.69 m. 2 The production method was the same as in Example 1 in Table 1, except that the electrode composition was 0.1C / g, Dn10 was 2.8 μm, the 0.1C discharge capacity at 0.05 to 2.0 V was 357.8 mAh / g, and the initial coulombic efficiency was 95.9%.
[0130] Battery Testing (1) 0.8V specific capacity of button-type half cell and its initial coulombic efficiency The test method is as follows. The negative electrode plates manufactured in each of the above examples and comparative examples were punched into disk samples with a diameter of 14 mm for use. A 14 mm lithium sheet was used as the counter electrode. EC, DEC, and DMC were mixed uniformly in equal volumes, and then 1 mol / L LiPF6 was uniformly dissolved in the organic solvent to prepare an electrolyte. Each of the disk samples, a separator, and a lithium sheet were laminated in this order to manufacture an electrode group, and the electrolyte was injected into the electrode group to complete the manufacture of a button battery. The above operations were performed in a glove box. The button battery was discharged at a constant current of 0.1C to a voltage of 0.005V in a constant temperature environment of 25°C, then discharged at a constant voltage of 0.005V until the current became 0.01mA or less, and then left to stand for 5min. The discharge capacity at this time was taken as d0. Next, the battery was charged at a constant current of 0.1C to a voltage of 0.8V. The charge capacity at this time was taken as the initial specific capacity, C0.8V. The initial coulombic efficiency at 0.8V was ice0.8V=C0.8V / d0×100%.
[0131] (2) Testing the cycle characteristics of secondary batteries at 45°C The secondary batteries manufactured in the above Examples and Comparative Examples were charged at a constant current of 1C to a voltage of 4.25V in a constant temperature environment of 45°C, then charged at a constant voltage of 4.25V until the current was 0.05mA or less, then left to stand for 5min, then discharged at a constant current of 1C to a voltage of 2.5V, and left to stand for 5min, which is one charge-discharge cycle, and the discharge capacity this time was the discharge capacity of the first cycle of the secondary battery. The secondary batteries were subjected to a 300-cycle charge-discharge test according to the above method, and the discharge capacity at the 300th cycle was recorded.
[0132] Capacity retention rate of a secondary battery after 300 cycles at 45°C CR45°C (%) = discharge capacity at 300th cycle / discharge capacity at 1st cycle × 100%.
[0133] (3) Testing the cycle expansion characteristics of secondary battery plates at 45°C The thickness of the negative electrode plate of the secondary battery after the cold pressing process was defined as h0, and the secondary battery was subjected to a 300cls cycle according to the above-mentioned test method for cycle characteristics of the secondary battery at 45°C, and was charged at a constant current of 1C rate to a voltage of 4.25V, then charged at a constant voltage of 4.25V until the current became 0.05mA or less, and then left to stand for 5min. The electrode group after the cycle was disassembled in a drying room, and the thickness of the negative electrode plate after the 300cls cycle was defined as h300, and the 300cls cycle expansion rate of the secondary battery plate at 45°C was Δh300(%)=(h300-h0) / h0*100%.
[0134] In Examples 2 to 21 and Comparative Examples 2 to 3, the manufacturing methods are similar to those of the secondary battery in Example 1, but important parameters for manufacturing the negative electrode plate were adjusted, as shown in Table 1.
[0135] [Table 1-1] [Table 1-2]
[0136] As can be seen from the above results, in Examples 1 to 9, as the proportion of silicon material in the first negative electrode film layer increased, the 0.8 V specific capacity of the negative electrode plate was clearly improved, and the 45°C-300cls cycle capacity retention rate and expansion rate were good.
[0137] As can be seen from Examples 10 to 15, with an increase in the thickness of the first negative electrode film layer, the 0.8V specific capacity of the negative electrode plate was significantly improved, but the 45°C-300cls cycle capacity retention rate was significantly decreased, and the expansion rate was significantly increased. Considering the overall characteristics of the battery, the thickness of the first negative electrode film layer is preferably 15μm or less, and in particular, the thickness of the first negative electrode film layer is more preferably 5μm to 15μm, for example 5.9μm to 13μm.
[0138] As can be seen from Examples 16 to 21, when the SP in the first negative electrode film layer was partially replaced with artificial graphite, the 0.8V specific capacity of the negative electrode plate was slightly improved, and the 45°C-300cls cycle capacity retention rate was somewhat reduced with the decrease in the artificial graphite particle size, but the expansion rate was somewhat improved. In consideration of the overall battery characteristics, the particle size of the artificial graphite is preferably 10μm or less, and in particular, the particle size of the artificial graphite is more preferably 8μm or less, for example, 2μm to 5μm.
[0139] In Comparative Example 1, in which ordinary artificial graphite was blended with a high content of silicon, the 0.8V specific capacity of the negative plate was slightly reduced, and compared with Example 8, which had the same blending ratio of silicon, the 45°C-300cls cycle capacity retention rate was significantly reduced and the cycle expansion rate was significantly increased. This shows that the solution of the present application can effectively improve the cycle capacity retention rate and the cycle expansion rate.
[0140] In Comparative Example 2, in which the SP content in the first negative electrode film layer was reduced and the CNT content was increased, the 0.8V specific capacity of the negative electrode plate was slightly reduced, the 45°C-300cls cycle capacity retention rate was deteriorated, and the cycle expansion rate was large. In addition, the results of the experiment showed that a high content of CNT is prone to gelation when stirring to produce a slurry, and this solution is expensive, but the solution of the high content of SP of the present application can solve the above problems.
[0141] In Comparative Example 3, in which the content of the first conductive agent SP in the first negative electrode film layer was reduced, the 0.8 V specific capacity of the negative electrode plate was seriously affected, the 45°C-300cls cycle capacity retention rate was seriously deteriorated, and the cycle expansion rate was large. This shows that the content of the first conductive agent SP is very important for the capacity of the negative electrode plate and for improving the cycle stability and cycle expansion.
[0142] The present application is not limited to the above-mentioned embodiment. The above-mentioned embodiment is merely an example, and any embodiment having substantially the same configuration as the technical idea and exhibiting the same action or effect within the scope of the technical proposal of the present application is included in the technical scope of the present application. In addition, other forms formed by making various modifications to the embodiment that a person skilled in the art can conceive, or by combining some of the components in the embodiment, within the scope of the purpose of the present application, are also included in the scope of the present application. [Explanation of symbols]
[0143] REFERENCE SIGNS LIST 1 battery pack; 2 upper housing; 3 lower housing; 4 battery module; 5 secondary battery; 51 case; 52 electrode assembly; 53 cover plate; 600 current collector; 601 first negative electrode film layer; 602 second negative electrode film layer.
Claims
1. A secondary battery, The negative electrode plate includes: A negative electrode current collector; a first negative electrode film layer provided on at least one surface of the negative electrode current collector; A second negative electrode film layer provided on a surface of the first negative electrode film layer, the first negative electrode film layer includes a first negative electrode active material and a first conductive agent, the first negative electrode active material includes a silicon-based material, and the first conductive agent includes one or more of conductive carbon black, graphite, and carbon nanotubes; The mass ratio of the silicon-based material in the first negative electrode film layer is 40% to 50%, and the mass ratio of the first conductive agent in the first negative electrode film layer is 25% to 40%, The thickness of the first negative electrode film layer is 5.9 μm to 13 μm, a second negative electrode film layer including a second negative electrode active material, a second conductive agent, and a second binder, the second negative electrode active material including artificial graphite and a second silicon-based material, a mass ratio of the artificial graphite in the second negative electrode active material being 80% or more, and a mass ratio of the second silicon-based material in the second negative electrode film layer being 8% or less.
2. The secondary battery according to claim 1 , wherein the first conductive agent contains conductive carbon black, and the mass ratio of the first conductive agent in the first negative electrode film layer is 20% or more.
3. 3. The secondary battery according to claim 2, wherein the mass ratio of the conductive carbon black in the first negative electrode film layer is 20% to 40%.
4. 4. The secondary battery according to claim 3, wherein the mass ratio of the conductive carbon black in the first negative electrode film layer is 23% to 35%.
5. The secondary battery according to any one of claims 1 to 4, wherein the first conductive agent contains carbon nanotubes, and a mass ratio of the first conductive agent in the first negative electrode film layer is 0.4% or less.
6. 6. The secondary battery according to claim 5, wherein a mass ratio of the carbon nanotubes in the first negative electrode film layer is 0.1% to 0.3%.
7. The secondary battery according to any one of claims 1 to 6, wherein the first conductive agent contains graphite, and the graphite has a volume average particle diameter Dv50 of 8 µm or less.
8. The secondary battery according to claim 7, wherein the graphite has a volume average particle diameter Dv50 of 2 μm to 5 μm.
9. The secondary battery according to any one of claims 1 to 8, wherein the first conductive agent contains graphite, and a mass ratio of the graphite in the first conductive agent is 10% or less.
10. The secondary battery according to claim 9, wherein a mass ratio of the graphite in the first conductive agent is 3% to 8%.
11. The secondary battery according to any one of claims 1 to 10, wherein the first negative electrode film layer contains a first binder, and a mass ratio of the first binder in the first negative electrode film layer is 15% or more.
12. The secondary battery according to claim 11, wherein a mass ratio of the first binder in the first negative electrode film layer is 18% to 25%.
13. The secondary battery according to any one of claims 1 to 12, wherein a ratio of a thickness of the first negative electrode film layer to a thickness of the second negative electrode film layer is 1:2 or less.
14. 14. The secondary battery according to claim 13, wherein a ratio of a thickness of the first negative electrode film layer to a thickness of the second negative electrode film layer is 1:12 to 1:
3.
15. 15. The secondary battery according to claim 1, wherein a ratio of an areal density of the first negative electrode film layer to an areal density of the second negative electrode film layer is 1:3 or less.
16. 16. The secondary battery according to claim 15, wherein a ratio of an areal density of the first negative electrode film layer to an areal density of the second negative electrode film layer is 1:9 to 1:
3.
17. The volume average particle diameter Dv50 of the artificial graphite is 10 μm to 20 μm, And / or, the Dn10 of the artificial graphite is 1 μm to 5 μm, And / or the specific surface area of the artificial graphite is 0.5 m 2 / g to 1.5m 2 / g, And / or the initial coulombic efficiency of the artificial graphite is 94.5% to 96.5%.
18. The volume average particle diameter Dv50 of the artificial graphite is 13 μm to 18 μm, And / or, the Dn10 of the artificial graphite is 2 μm to 3 μm, And / or the specific surface area of the artificial graphite is 0.6 m 2 / g to 1.0 m 2 / g, And / or the initial coulombic efficiency of the artificial graphite is 95.0% to 96.0%.
19. A power consuming device comprising the secondary battery according to any one of claims 1 to 18.
Citation Information
Patent Citations
Porous silicon-based cathode for lithium battery and preparation method thereof
CN101894940A
Flexible integrated thin-film lithium-sulfur or lithium ion battery cell, battery and preparation method thereof
CN106252659A
Negative plate and secondary battery
CN111640913A
Anode active material and preparation method thereof, and device using the anode active material
WO2020186799A1
Secondary battery and fabrication method therefor, and apparatus containing secondary battery
WO2021217639A1